How has research on the effectiveness and safety of COVID-19 vaccination been evaluated: a scope review with emphasis on CoronaVac - Alzate-Ángel, Juan C.; Avilés-Vergara, Paula A.; Arango-Londoño, David; Concha-Eastman, Alberto; Garcés-Hurtado, Anthony; López-Carvajal, Liliana; Minotta, Ingrid L.; Ortega-Lenis, Delia; Quintero, Geraldine; Reina-Bolaños, Sebastián; Reina-Bolaños, Carlos A.; Roa, Pablo; et al. (Frontiers in Public Health, 2024)
Introduction The control of the COVID-19 epidemic has been focused on the development of vaccines against SARS-CoV-2. All developed vaccines have reported safety and efficacy results in preventing infection and its consequences, although the quality of evidence varies depending on the vaccine considered. Different methodological designs have been used for their evaluation, which can influence our understanding of the effects of these interventions. CoronaVac is an inactivated vaccine, and it has been assessed in various studies, including clinical trials and observational studies. Given these differences, our objective was to explore the published information to answer the question: how has the efficacy/effectiveness and safety of CoronaVac been evaluated in different studies? This is to identify potential gaps and challenges to be addressed in understanding its effect. Methods A scoping review was carried out following the methodology proposed by the Joanna Briggs Institute, which included studies carried out in humans as of 2020, corresponding to systematic reviews, clinical trials, analytical or descriptive observational studies, in which the effectiveness and/or safety of vaccines for COVID19 were evaluated or described. There were no age restrictions for the study participants. Results The efficacy/effectiveness and safety of this vaccine was assessed through 113 studies. Nineteen corresponded to experimental studies, 7 of Phase II, 5 of Phase IV, and 4 were clinical trials with random assignment. Although some clinical trials with random assignment have been carried out, these have limitations in terms of feasibility, follow-up times, and with this, the possibility of evaluating safety outcomes that occur with low frequencies. Not all studies have used homogeneous methods of analysis. Both the prevention of infection, and the prevention of outcomes such as hospitalization or death, have been valued through similar outcomes, but some through multivariate analysis of dependencies, and others through analysis that try to infer causally through different control methods of confounding. Conclusion Published information on the evaluation of the efficacy/effectiveness and safety of the CoronaVac is abundant. However, there are differences in terms of vaccine application schedules, population definition, outcomes evaluated, follow-up times, and safety assessment, as well as non-standardization in the reporting of results, which may hinder the generalizability of the findings. It is important to generate meetings and consensus strategies for the methods and reporting of this type of studies, which will allow to reduce the heterogeneity in their presentation and a better understanding of the effect of these vaccines.